Alignment of the tibial component in total knee arthroplasty procedures using an intramedullary or extramedullary guide: double-blind randomized prospective study - Bruno da Rocha Moreira Rezende; Thiago Fuchs; Rodrigo Nishimoto Nishi; Munif Ahmad Hatem; Luciana Mendes Ferreira da Silva; Rogério Fuchs; Paulo Gilberto Cimbalista de Alencar (Revista Brasileira de Ortopedia, 2015)
OBJECTIVES: To evaluate the results obtained through using an intramedullary or extramedullary guide for sectioning the tibia in total knee arthroplasty procedures, with a view to identifying the accuracy of these guides and whether one might be superior to the other.METHODS: This was a randomized double-blind prospective study on 41 total knee arthroplasty procedures performed between August 2011 and March 2012. The angle between the base of the tibial component and the mechanical axis of the tibia was measured during the immediate postoperative period by means of radiography in anteroposterior view on the tibia that encompassed the knee and ankle.RESULTS: There was no demographic difference between the two groups evaluated. The mean alignment of the tibial component in the patients of group A (intramedullary) was 90.3° (range: 84-97°). In group B (extramedullary), it was 88.5° (range: 83-94°).CONCLUSION: In our study, we did not find any difference regarding the precision or accuracy of either of the guides. Some patients present an absolute or relative contraindication against using one or other of the guides. However, for the other cases, neither of the guides was superior to the other one.